Genome Mining and Expression Analysis of Carboxylesterase and Glutathione S-Transferase Genes Involved in Insecticide Resistance in Eggplant Shoot and Fruit Borer, Leucinodes orbonalis (Lepidoptera: Crambidae) - Kariyanna, B.; Prabhuraj, A.; Asokan, R.; Agrawal, A.; Gandhi Gracy, R.; Jyoti, P.; Venkatesan, T.; Bheemanna, M.; Kalmath, B.; Diwan, J. R.; Pampanna, Y.; Mohan, M. (Frontiers in Physiology, 2020)
The shoot and fruit borer, Leucinodes orbonalis (Lepidoptera: Crambidae) is the major cause of low productivity in eggplant and insecticides being the mainstay of management of L. orbonalis. However, field control failures are widespread due to the evolution of insecticide resistance. Taking advantage of the whole genome sequence information, the present study investigated the level of insecticide resistance and the expression pattern of individual carboxylesterase (CE) and glutathione S-transferases (GSTs) genes in various field collected populations of L. orbonalis. Dose-mortality bioassays revealed a very high level of resistance development against fenvalerate (48.2–160-fold), phosalone (94-534.6-fold), emamectin benzoate (7.2–55-fold), thiodicarb (9.64–22.7-fold), flubendiamide (187.4–303.0-fold), and chlorantraniliprole (1.6–8.6-fold) in field populations as compared to laboratory-reared susceptible iso-female colony (Lo-S). Over-production of detoxification enzymes viz., CE and GST were evident upon enzyme assays. Mining of the draft genome of L. orbonalis yielded large number of genes potentially belonging to the CE and GST gene families with known history of insecticide resistance in other insects. Subsequent RT-qPCR studies on relative contribution of individual genes revealed over-expression of numerous GSTs and few CEs in field populations, indicating their possible involvement of metabolic enzymes in insecticide resistance. The genomic information will facilitate the development of novel resistance management strategies against this pest.